Exocrine scent marking: Coordinative role of arginine vasopressin in the systemic regulation of social signaling behaviors. (May 2022) - Arakawa, Hiroyuki; Higuchi, Yuki
Abstract: Arginine vasopressin (AVP) is a neurohypophysial hormone that coordinatively regulates central socio-emotional behavior and peripheral control of antidiuretic fluid homeostasis. Most mammals, including rodents, utilize exocrine or urine-contained scent marking as a social signaling tool that facilitates social adaptation. The exocrine scent marking behavior is postulated to fine-tune sensory and cognitive abilities to recognize key social features via exocrine/urinary olfactory cues and subsequently control exocrine deposition or urinary marking through the mediation of osmotic fluid balance. AVP is implicated as a major player in controlling both recognition and signaling responses. This review provides constructive hypotheses on the coordinative processes of the AVP neurohypophysial circuits in the systemic regulations of fluid control and social-communicative behavior, via the expression of exocrine scent marking, and further emphasizes a potential role of AVP in a common mechanism underlying social communication in rodents. Highlights: Arginine vasopressin regulates systemic processes in the production of exocrine scent marking. Central vasopressin neuronal circuits coordinatively control scent marking behavior. Peripheral vasopressin mediates physiological mode from voiding to marking.